Conformational and Functional Effects Induced by D- and L-Amino Acid Epimerization on a Single Gene Encoded Peptide from the Skin Secretion of Hypsiboas punctatus - de Magalhães, Mariana T. Q.; Barbosa, Eder A.; Prates, Maura V.; Verly, Rodrigo M.; Munhoz, Victor Hugo O.; de Araújo, Ivan E.; Bloch, Carlos, Jr (PLOS ONE, 2013)
Skin secretion of Hypsiboas punctatus is the source of a complex mixture of bioactive compounds where peptides and small proteins prevail, similarly to many other amphibians. Among dozens of molecules isolated from H. punctatus in a proteomic based approach, we report here the structural and functional studies of a novel peptide named Phenylseptin (FFFDTLKNLAGKVIGALT-NH2) that was purified as two naturally occurring D- and L-Phes configurations. The amino acid epimerization and C-terminal amidation for both molecules were confirmed by a combination of techniques including reverse-phase UFLC, ion mobility mass spectrometry, high resolution MS/MS experiments, Edman degradation, cDNA sequencing and solid-phase peptide synthesis. RMSD analysis of the twenty lowest-energy 1H NMR structures of each peptide revealed a major 90° difference between the two backbones at the first four N-terminal residues and substantial orientation changes of their respective side chains. These structural divergences were considered to be the primary cause of the in vitro quantitative differences in antimicrobial activities between the two molecules. Finally, both molecules elicited equally aversive reactions in mice when delivered orally, an effect that depended entirely on peripheral gustatory pathways.